Analysis of English for International Communication (EIC) Research Projects Conducted in the Independent Study (IS) Course Underpinning the Thailand 20-Year National Strategy Plan - Patcharin Kangkha; Chariya Songpra; Kanjanarat Urairat (English Education Journal, 2023)
The main focuses of this research study were to identify all research projects conducted by English for International Communication (EIC) students between 2017-2019 based on the Thailand 20-Year National Strategy Plan; summarize and analyzing; and, suggest the scope of the research projects in the IS course. A total of 109 research projects proceeded by the EIC students were analyzed. The research instruments were the Research Topic Analysis Checklist (RTAC). The statistic used in data analysis was the percentage. Overall, the findings indicated that the most of the research projects were in the strategy of development and strengthening human capital (85%), social cohesion and just society (5.45%), and national competitiveness enhancement (1.09%) respectively whereas there was at 8.21% ungrouped projects. Noticeably, an innovation technology and area base of IS projects gradually increased with the 21st century skills in 2019. Additionally, the understanding of both university mission and Thailand 20-Year National Strategy Plan related to the various research projects. This study can mutually provide a practical guideline for encouraging both teachers and students to explore more diverse interesting topic areas by bridging the gaps between the university mission, provincial policy and strategy, and Thailand 20-Year National Strategy Plan.